2006
DOI: 10.1016/j.neuroscience.2006.01.040
|View full text |Cite
|
Sign up to set email alerts
|

The aging hippocampus: A multi-level analysis in the rat

Abstract: The purpose of the current thesis was twofold: (1) to examine various factors that might be contributing to age-related learning and memory deficits specifically related to the hippocampus, and (2) to validate our rat model of aging, employing a multilevel analysis. We found age-related deficits on both spatial and non-spatial hippocampus-dependent tasks that were accompanied by structural alterations observed both in vivo (volume, but not neuronal metabolic function) and post mortem (neuronal density and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
133
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 202 publications
(338 reference statements)
14
133
1
Order By: Relevance
“…DCX immunoreactive cells were found to decrease with age in both groups. This result concurs with previous studies which found that neurogenesis dramatically declined in the dentate gyrus during aging [5,7,11,12,17,23,25,28]. In addition, Kronenberg et al [16] compared young adult SHR and stroke-prone SHR (SHRSP) with the genetic control WKY strain: in both SHR and SHRSP, newly generated DCX immunoreactive neurons were significantly high compared to WKY strain.…”
Section: Discussionsupporting
confidence: 90%
“…DCX immunoreactive cells were found to decrease with age in both groups. This result concurs with previous studies which found that neurogenesis dramatically declined in the dentate gyrus during aging [5,7,11,12,17,23,25,28]. In addition, Kronenberg et al [16] compared young adult SHR and stroke-prone SHR (SHRSP) with the genetic control WKY strain: in both SHR and SHRSP, newly generated DCX immunoreactive neurons were significantly high compared to WKY strain.…”
Section: Discussionsupporting
confidence: 90%
“…A common characteristic of advancing age is a gradual decline in cognitive functions associated with the progressive reduction of structural and functional plasticity in brain regions such as cerebral cortex and hippocampus that play a key role in cognition (Benice et al 2006;Driscoll et al 2006;Hara et al 2012; Van der Jeugd et al 2013). Studies in rats and non-human primates have demonstrated that aging impairs the functional integrity of prefrontal cortex neurons (Morrison and Baxter 2012) which is associated with decline in structural plasticity and cognitive performance (Dumitriu et al 2010;Bloss et al 2011Bloss et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…These changes cannot be attributed to any age-related difference in hippocampal volume because, although a decrease in cortical thickness was observed, we found no evidence of any difference in hippocampal volume in aged, compared with young, rats. However, analysis using a 9.4 Tesla magnet revealed an age-dependent decrease in hippocampal volume of Fisher 344 ϫ Brown Norway hybrid rats (Driscoll et al, 2006), suggesting that there may be strain differences between these rats and the Wistar rats used here, or that the field strength used in this study may not be strong enough to highlight subtle volumetric differences.…”
Section: Discussionmentioning
confidence: 74%